A prototype for multi-agent islands recommender / Maskina Rezali - Rezali, Maskina (2004)
Nowadays, the internet becomes a popular medium to communicate each others. The internet has been used in many sectors especially in business. The tourism sectors also have involved in this rapid growth of internet. The main objectives of developing the tourism web-based are to find a suitable and worthwhile vacation or holiday packages. With the creation of this prototype, it is hope that it can fulfill its objective. The objective of Prototype for Multi-Agent Island Recommender is to assist tourist find the suitable place to visit based on their requirements. The prototype will solve the user's problem by having their preferences that will be executed to find the nearest match result in the database. The result will be displayed to the users as the best suggestion by this prototype.